A review of key power system stability challenges for large-scale PV integration - Shah R.; Mithulananthan N.; Bansal R.C.; Ramachandaramurthy V.K. (Elsevier Ltd, 2023)
Grid codes; Large-scale PV; Power system stability; Reactive power support; Models